Antimicrobial activity of Cassia grandis L. f. - Delgado, Alexandra Quesada; Pesantes Domínguez, Oswaldo; Bustamante Pesantes, Katherine; Auxiliadora Alarcón, María; Tafur Recalde, Valdano (Revista Universidad de Guayaquil, 2016)
Antimicrobial and antifungal activity in vitro was investigate by agar diffusion method, the methanol extracts, ethanolic and aqueous-alcoholic fruit of Cassia grandis L, known as fistula cane in the Ecuadorian coast, belonging to the family Leguminosae, collected on the premises of the Citadel "Salvador Allende" University of Guayaquil. The microorganisms used, from the Microbiology Laboratory were: Klebsiella pneumoniae, Mycobacterium smegmatis, Pseudomonas aeruginosa, Escherichia coli, Salmonella enteritidis. Salmonella typni, Salmonella gallinarum, Staphylococcus aureus and Proteus vulgaris. The positive control was Streptomycin Sulfate. Alkaloids, antnraquinones, fixed oils and essential, antnraquinones, coumarins, steroids, flavonoias, cyanogenic glycosides ana cardiac, Triterpenoids, tannins ana saponins sesquiterpenlactones: a phytochemical study was further conduct. Proteus vulgaris, Staphylococcus aureus and Salmonella enteritidis: antimicrobial action was found. Significant evidence for saponin, tannins and alkaloids anthraquinones lesser extent, followed by glycosides, flavonoids and sesquiterpene lactone was found.
Keywords: Cassia grandis L; antimicrobial and antifungal activity; a gar difusión method; Antioxidant activity; streptomycin sulfate